Helicobacter pylori CagA Translocation Is Closely Associated With the Expression of CagA-signaling Molecules in Low-grade Gastric Mucosa-associated Lymphoid Tissue Lymphoma. (June 2015) - Kuo, Sung-Hsin; Yeh, Kun-Huei; Chen, Li-Tzong; Lin, Chung-Wu; Hsu, Ping-Ning; Wu, Ming-Shiang; Liou, Jyh-Ming; Tsai, Hui-Jen; Tzeng, Yi-Shin; Cheng, Ann-Lii
Abstract : We previously reported that the direct contact of Helicobacter pylori (HP) and B cells results in CagA translocation into the latter and that the translocated CagA regulates intracellular signaling pathways. Similarly, we recently found that CagA does exist in the malignant B cells of gastric mucosa-associated lymphoid tissue (MALT) lymphoma and that its presence is closely associated with HP dependence. In this study, we further evaluated whether CagA expression regulates signal transduction molecules in the tumor cells and further contributes to the lymphomagenesis of HP-dependent growth of gastric MALT lymphoma. Forty-seven patients with stage IE HP-positive gastric MALT lymphoma who received HP eradication as their frontline therapy were included. The expression of CagA and signaling pathway–related proteins, such as phospho-SHP-2 (p-SHP-2), p-ERK, p-p38 MAPK, Bcl-2, and Bcl-xL, in tumor cells was evaluated by immunohistochemistry. There were 25 HP-dependent and 22 HP-independent cases. We observed that the CagA expression rate was significantly higher in HP-dependent than in HP-independent tumors (72% [18/25] vs. 18.2% [4/22]; P <0.001). The expression of CagA was closely associated with p-SHP-2 ( P =0.012), p-ERK ( P =0.002), p-p38 MAPK ( P =0.006), Bcl-2 ( P =0.020), and Bcl-xL ( P =0.006) expression. Spearman correlation coefficient analysis showed a strong correlation between CagA and signaling molecule expression. Combined CagA expression, p-SHP-2 expression, and p-ERK expression showed an increased positive predictive value (93.3% [14/15] vs. 81.8% [18/22]) and an increased specificity (95.5% [21/22] vs. 81.8% [18/22]) for HP dependence compared with CagA expression alone. Our results indicate that CagA protein expression is biologically relevant and is associated with the activation of its downstream signals in HP-dependent gastric MALT lymphoma. Abstract : Supplemental Digital Content is available in the text.